Relation Between Multiplication of Venous Carbon Dioxide Partial Pressure (PvCO2) and the Ratio of Gas Flow to Pump Flow (Ve/Q) with Hyperlactatemia During Cardiopulmonary Bypass - Yos Kowara; Philia Setiawan; Prananda S. Airlangga; Kun A. Abbas; Fajar Perdhana; Teuku A Husain; Bambang P. Semedi (Annals of Cardiac Anaesthesia)
Background: The incidence of hyperlactatemia due to hypoperfusion during cardiopulmonary bypass (CPB) increases morbidity. Carbon dioxide production during CPB is one of the lactate production markers, in addition to other markers such as delivery oxygen (DO2), oxygen consumption (VO2), mixed vein oxygen saturation (SvO2), and oxygen extraction ratio (O2ER). Method: This observational analytic study was conducted on 40 adult cardiac surgery patients using a CPB machine. Initial lactate is taken when entering CPB and final lactate is examined 15 min after coming off bypass. The values of DO2, VO2, SvO2, VCO2, respiratory quotient (RQ), DO2/VCO2, PvCO2 × Ve/Q were calculated from the results of blood and venous gas analysis 1 h after entering CPB in the nadir of core temperature and lowest pump flow. Result: The multivariate test showed that the value of PvCO2 × Ve/Q was more effective than other oxygenation and carbon dioxide parameters in predicting an increase in the percentage of lactate. Each increase of 1 mmHg PvCO2 ×× Ve/Q can predict a final lactate increase of 29% from the initial lactate. The high PvCO2 × Ve/Q value is also the strongest correlation factor for the incidence of hyperlactatemia after CPB (final lactate >3 mmol/L). The cutoff value of this marker is >19.3 mmHg, which has a sensitivity of 100% and a specificity of 55.6% with a strong correlation value. Conclusion: The PvCO2 × Ve/Q value proved to be one of the significant markers in predicting hyperlactatemia during cardiac surgery using CPB.